2015
DOI: 10.1371/journal.pone.0118550
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Neurogenesis during Experimental Autoimmune Encephalomyelitis Reveals Pitfalls of Bioluminescence Imaging

Abstract: Bioluminescence imaging is a sensitive approach for longitudinal neuroimaging. Transgenic mice expressing luciferase under the promoter of doublecortin (DCX-luc), a specific marker of neuronal progenitor cells (NPC), allow monitoring of neurogenesis in living mice. Since the extent and time course of neurogenesis during autoimmune brain inflammation are controversial, we investigated neurogenesis in MOG-peptide induced experimental allergic encephalomyelitis (EAE) using DCX-luc reporter mice. We observed a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…We have previously shown that at the acute phase, the absolute number of DCX 1 cells was not different between EAE and control animals in the dorsal DG (Giannakopoulou et al, 2013), a finding that has already been addressed by others (Ayzenberg et al, 2015). However, in the present study we found that the DCX 1 cells increased in EAE mice during the recovery phase.…”
Section: Discussionsupporting
confidence: 72%
“…We have previously shown that at the acute phase, the absolute number of DCX 1 cells was not different between EAE and control animals in the dorsal DG (Giannakopoulou et al, 2013), a finding that has already been addressed by others (Ayzenberg et al, 2015). However, in the present study we found that the DCX 1 cells increased in EAE mice during the recovery phase.…”
Section: Discussionsupporting
confidence: 72%
“…This model was proposed to be a functional and valuable tool for monitoring whole‐body in vivo inflammation in various disease models including EAE (Hayashi et al, ; Li et al, ; Yang et al, ). Moreover, bioluminescence imaging was used to track the transplanted human embryonic stem cell–derived oligodendrocyte progenitors and neural stem cells during EAE (Ayzenberg et al, ; Stefferl, Brehm, et al, ). By expressing firefly luciferase under the IL‐6 promoter, Hayashi et al were able to show bioluminescence in the spinal cord and brain in the EAE mice (Hayashi et al, ).…”
Section: Next‐generation Animal Models Of Msmentioning
confidence: 99%
“…Although bioluminescence imaging in EAE was recently proposed to have its shortcomings (Ayzenberg et al, ), it may be a valuable tool in animal model research of MS, especially when validated by other tools like magnetic resonance imaging and histology (Guglielmetti et al, ).…”
Section: Next‐generation Animal Models Of Msmentioning
confidence: 99%
“…A study using an Experimental Autoimmune Encephalomyelitis (EAE) model in Dcx‐Luc mice already described an increase in BLI signal unrelated to neurogenesis, which followed the same temporal pattern as the opening of the BBB (Ayzenberg et al ., ). Nevertheless, more research is needed to determine the impact of BBB alterations on substrate/tracer availability in different models and diseases.…”
Section: Discussionmentioning
confidence: 97%